Enhancing Student Literacy With the “Go to Mier” and Reading Corner Program at SD Muhammadiyah 3 Wage: Penguatan Literasi Siswa Dengan Program Go To Mier Dan Pojok Baca Di SD Muhammadiyah 3 Wage - Nuroh, Ermawati Zulikhatin; Arumdani, Dewi Kirana Putri; Anggraeni, Alvina Rizky Dwi; Septiani, Wulan Dwi; Farahdiba, Everyana Frienansia (Procedia of Social Sciences and Humanities, 2024)
This article aims to evaluate the effectiveness of the "Go to Mier" and "Reading Corner" programs in improving student literacy progress at SD Muhammadiyah 3 Wage. By using a combination of observation methods, and interviews. Data were obtained from student participation in both programs. Data analysis revealed that the "Go to Mier" program successfully increased students’ access to reading materials and broadened their reading interest. . On the other hand, the "Reading Corner" creates an environment that stimulates students’ reading interest in school. These findings have important implications for SD Muhammadiyah 3 Wage and other schools in the development of effective literacy programs. Recommendations for future program improvements include increasing the book collection, counseling, and training to school staff. For the implementation of the program in other schools, adaptation to the local context, active involvement of students, And cooperation with external parties is highly recommended. Thus, these measures are expected to make a significant contribution in improving student literacy and creating a stimulating learning environment in schools.